2018
DOI: 10.1051/matecconf/201820403016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced rooftop rainwater harvesting quality through filtration using zeolite and activated carbon

Abstract: This study aimed to investigate the quality of the rooftop rainwater harvesting (RRWH) and to treat it for clean water supply alternative of Graha Rektorat building at State University of Malang, Indonesia. Different combinations of zeolite and activated carbon were used as filter media to treat the RRWH. Several parameters have tested to investigate the quality of RRWH based on Permenkes RI No. 416 / MENKES / PER / IX / 1990. Most of the quality of the RRWH met clean water and drinking water standard. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Yulistyorini found that a combination of zeolite and activated carbon results in a 37% reduction in TDS and a 36% reduction of coliform, while pure zeolite only reduces KMnO4 by 35%. (Yulistyorini et al, 2018) Research by Shaheed tried to implement an adsorption-filtration system for rainwater that have high levels of NH 3 -N and E.coli. As a result, both parameter concentration was able to meet the clean water standard but not the drinking water standard.…”
Section: Concept Of Rainwater Harvestingmentioning
confidence: 99%
“…Yulistyorini found that a combination of zeolite and activated carbon results in a 37% reduction in TDS and a 36% reduction of coliform, while pure zeolite only reduces KMnO4 by 35%. (Yulistyorini et al, 2018) Research by Shaheed tried to implement an adsorption-filtration system for rainwater that have high levels of NH 3 -N and E.coli. As a result, both parameter concentration was able to meet the clean water standard but not the drinking water standard.…”
Section: Concept Of Rainwater Harvestingmentioning
confidence: 99%